Aesthetics of protest: an examination of the photojournalistic approach to protest imagery. (August 2017) - Veneti, Anastasia
Images of protests and demonstrations are crucial to both social movements and protesters who wish to communicate their identity and their messages to wider audiences. However, the photographing of such political events by press photographers is a complex process. The current analysis focuses on questions of aesthetics surrounding issues of visuality regarding protests and demonstrations. Based on empirical data from 17 semi-structured in-depth interviews with Greek photojournalists, this article examines what is photographed during a protest and how this is affected by the photojournalists' aesthetic criteria. Drawing on scholarly work on photojournalism (Ritchin and Åker) and photography (Sontag), the author discusses how, in addition to the presumption of the principle of recording reality, photojournalists' practice is also infused with subjective language and influenced by art photographers' techniques. Therefore, the main argument of this article is that the employment of hybridized photography practices by photojournalists can have an impact upon their visual decisions with regard to what and how is photographed during a protest. The product of such practices is usually high quality, captivating images with apparent affective qualities.